1D ferromagnetic edge contacts to 2D graphene/h-BN heterostructures. (3rd October 2017) - Karpiak, Bogdan; Dankert, André; Cummings, Aron W; Power, Stephen R; Roche, Stephan; Dash, Saroj P
Abstract: We report the fabrication of one-dimensional (1D) ferromagnetic edge contacts to two-dimensional (2D) graphene/h-BN heterostructures. While aiming to study spin injection/detection with 1D edge contacts, a spurious magnetoresistance signal was observed, which is found to originate from the local Hall effect in graphene due to fringe fields from ferromagnetic edge contacts and in the presence of charge current spreading in the nonlocal measurement configuration. Such behavior has been confirmed by the absence of a Hanle signal and gate-dependent magnetoresistance measurements that reveal a change in sign of the signal for the electron- and hole-doped regimes, which is in contrast to the expected behavior of the spin signal. Calculations show that the contact-induced fringe fields are typically on the order of hundreds of mT, but can be reduced below 100 mT with careful optimization of the contact geometry. There may be an additional contribution from magnetoresistance effects due to tunneling anisotropy in the contacts, which needs further investigation. These studies are useful for optimization of spin injection and detection in 2D material heterostructures through 1D edge contacts.